Novel sustainable biodiesel production from low-grade oleic acid via esterification catalyzed by characterized crystalline ZrO2/Al2O3 - Amal Alkahlawy; Amany Gaffer (BMC Chemistry)
Abstract The depletion of fossil fuels and growing environmental concerns necessitate the exploration of renewable energy sources. Biodiesel, a promising alternative fuel derived from sustainable feedstock, has attracted considerable attention. This study investigates the catalytic esterification of oleic acid, a readily available fatty acid, with ethanol for biodiesel production using a novel heterogeneous catalyst, ZrO2/Al2O3. Crystalline ZrO2/Al2O3 was successfully synthesized and characterized using X-ray diffraction (XRD), Brunauer–Emmett–Teller (BET) surface area analysis, and Fourier-transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS) and temperature programmed desorption NH3-TPD to understand its structural and textural properties. The characterized ZrO2/Al2O3 was then employed to catalyze the esterification reaction. The influence of reaction parameters, including temperature, alcohol-to-oleic acid molar ratio, and catalyst loading, was systematically evaluated. Under optimal conditions (70 °C, 10:1 alcohol-to-oleic acid molar ratio, and 4 wt% catalyst loading), a remarkable 90.5% conversion of oleic acid to biodiesel was achieved. Furthermore, the catalyst exhibited reusability, demonstrating its potential for sustainable biodiesel production from low-grade oleic acid feedstock.